Analisis Putusan Pengadilan Hubungan Industrial Nomor 46/Pdt.Sus-PHI/2023/PN Pbr Pada Pengadilan Negeri Pekanbaru Dalam Kasus Pemutusan Hubungan Kerja - Saputra, Rafi; Yetniwati, Yetniwati; Novianti, Novianti (Universitas Jambi, Fakultas Hukum, 2025)
The purpose of this research is to analyze the legal considerations in Decision Number 46/Pdt.Sus-PHI/2023/PN Pbr related to the case of termination of employment (PHK) between Yosep Primadona (worker) and PT Eluan Mahkota (employer). The problem of this research is how the legal considerations in Decision Number 46/Pdt.Sus-PHI/2023/PN Pbr are viewed from juridical, philosophical, and sociological aspects. Normative juridical research method using conceptual approach, statutory approach, and case approach. The legal materials used are primary and secondary legal materials. The results showed that the panel of judges decided that the mutations and layoffs carried out by the company were invalid because they were contrary to Article 32 of Law Number 13 of 2003 concerning Manpower. The judges' considerations cover three aspects, based on the juridical aspect, the mutations and layoffs did not fulfill legal procedures, including the absence of prior notification and violation of Company Regulations, based on the philosophical aspect, the decision is based on the principles of substantive justice, balance of rights, and respect for the dignity of workers, based on the sociological aspect, the decision pays attention to the social impact of layoffs on workers and emphasizes the importance of protecting workers' rights in industrial relations. This decision reflects the application of the principles of legal certainty, justice, and worker protection, as well as emphasizing that layoffs must be the last resort (ultima ratio).